Mapping ecosystem services in the Arctic by cross-cultural PPGIS - Hausner, Vera Helene; Schmidt, Jennifer Irene; Ehrich, Dorothee (2014)
Poster presented at the 20th International Symposium on Society and Resource Management,International Association of Society & Natural Resources, Hannover, 09.06-13.06, 2014.